Impact of climate change on cotton production in Bangladesh - Nadiruzzaman, Md; Rahman, Mahjabeen; Pal, Uma; Croxton, Simon; Rashid, Md Bazlur; Bahadur, Aditya; Huq, Saleemul (MDPI, 2021)
Bangladesh produces only 5% of the cotton she needs to sustain her readymade garments industries. The country has very limited agricultural land and cotton competes with other crops for this scarce land resource. On top of that, Bangladesh is regarded as a country where agriculture is highly vulnerable to the variabilities of weather patterns that result from climate change. Against this backdrop, to better understand the potential for the sustainable expansion of cotton production in Bangladesh, we examine cotton’s agricultural value chain and projected climate risks associated with different phases of the chain. We identified associated stakeholders at different phases of cotton production, engaged with them to understand climatic and non-climatic threats and developed an integrated set of recommendations for climate-risk management through improving the connection of producers to markets, increasing economic returns to small farmers, and improving efficiency along the value chain. We discussed our estimated climate projections with stakeholders to understand the challenges at different stages of production and marketing, and together explored and identified probable solutions. This research offers a new and evolving approach to assess climate change impact on agriculture utilizing a holistic approach, which could be adopted for other crops.